Analyzing the Evolution and the Future of the Internet Topology Focusing on Flow Hierarchy - Yu Nakata; Shin’ichi Arakawa; Masayuki Murata (Journal of Computer Networks and Communications)
In the Internet, Autonomous Systems (ASes) exchange traffic through interconnected links. As traffic demand increases, more traffic becomes concentrated on such links. The traffic concentrations depend heavily on the global structure of the Internet topology. Therefore, a topological evolution considering the global structure is necessary to continually accommodate future traffic amount. In this paper, we first develop a method to identify the hierarchical nature of traffic aggregation on the Internet topology and use this method to discuss the long-term changes in traffic flow. Our basic approach is to extract the “flow hierarchy,” which is a hierarchical structure associated with traffic aggregation. Our results show that the current connection policy will lead to a severe traffic concentration in the future. We then examine a new evolution process that attempts to reduce this traffic concentration. Our proposed evolution process increases the number of links in the deeper level in the hierarchy, thus relaxing the traffic concentration. We apply our evolution process to the Internet topology in 2000 and evolve this scenario over 13 years. The results show that our evolution process could reduce the traffic concentration by more than half compared with that without our evolution process.